Case series of cutaneous Langerhans cell histiocytosis in Indonesian children; The clinicopathological spectrum (Dermatology Reports, 2020)
Langerhans Cell Histiocytosis (LCH) is a rare disease characterized by the clonal proliferation of Langerhans cells, which are immunoreactive to S-100 and CD-1a/ CD207 (Langerin). Cutaneous involvement is the most common presentation of LCH in children. It is suggested that the patients with single-system LCH limited to the skin have a better prognosis than those with systemic involvement. Three histologic reactions of cutaneous LCH have been reported and are associated with the clinical types of LCH. These histological reactions include: proliferative, granulomatous, and xanthomatous. This study presents the clinicopathological features of ten cutaneous LCH cases collected from Dr. Sardjito General Hospital Yogyakarta Indonesia between 2014-2018. The ten cases showed various clinical features, in which some features mimic other diseases. The microscopic features of skin biopsies showed granulomatous reaction in 80% of cases and proliferative reaction in the other 20%. Five patients (50% of cases) who died had systemic manifestation of thrombocytopenia, anemia, icterus, hepatosplenomegaly, and revealed the granulomatous type from their skin biopsy specimens. The clinical recognition of LCH and subsequent histological reaction determination are important since some cases may develop multisystem disease and have a poor prognosis.